DUKUNGAN SOSIAL DAN STRATEGI COPING PARA LANSIA - Siti Rohmah Nurhayati (Jurnal Penelitian Humaniora, 2012)
The aims of this study were to identify the problems in the elderly, prove the relationship between social-support and coping strategies in the elderly, describe the social support received by the elderly, and describe the patterns of coping strategies in the elderly related with social support received by the elderly. The primary data source was a quantitative survey with 30 elderly in the Posyandu Lansia Ketonggo Wonokromo Pleret Bantul. Data were collected by questioner and analyzed by regression and descriptive analysis. Results indicated that the problems experienced by the majority of elderly in this study were a disorder of the muscles, instability of the body, decreasing in the sensory function, cataracts or nearsightedness, tiredness, lack of finance, difficulties in managing money, as well as using the telephone. A significant positive correlation between social support and problem focused coping and a significant negative correlation between social support and emotion focused coping were confirmed. Social support was high enough on the subject, particularly the family support and support from significant other. The pattern of use of problem focused coping can be predicted from general social support and particularly from the support of friends, while the use of emotion focused coping can be predicted from social support in general and particularly from significant other support